2016
DOI: 10.1038/tp.2016.156
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial damage in major depression patients is modulated by SSRI treatment, as demonstrated by circulating biomarkers and an in vitro cell model

Abstract: There is a link between depression, cardiovascular events and inflammation. We have explored this connection through endothelial dysfunction, using in vivo and in vitro approaches. We evaluated circulating biomarkers of endothelial dysfunction in patients with major depression at their diagnosis (MD-0) and during antidepressant treatment with the selective serotonin reuptake inhibitor escitalopram, for 8 and 24 weeks (MD-8 and MD-24). Results were always compared with matched healthy controls (CON). We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 46 publications
2
50
0
2
Order By: Relevance
“…Interestingly, there was no significant dose‐response to either drug for trophoblast cells, while ECs appeared to have a dose‐response, where low drug doses caused higher than baseline TGFβ secretions while higher dosages reduced these secretions to a baseline level over time. This time and dose‐dependent response is intriguing as others have previously shown that SSRI treatment changes cell physiology, both in vivo in depressed patients and in vitro following exposure to serum from depressed patients, where SSRI treatment leads to a return to baseline levels over time . Given that TGFβ is important for survival, homeostasis and barrier function of ECs, as well as angiogenesis, it is interesting that these drugs can elicit a time and dose‐dependent effect .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Interestingly, there was no significant dose‐response to either drug for trophoblast cells, while ECs appeared to have a dose‐response, where low drug doses caused higher than baseline TGFβ secretions while higher dosages reduced these secretions to a baseline level over time. This time and dose‐dependent response is intriguing as others have previously shown that SSRI treatment changes cell physiology, both in vivo in depressed patients and in vitro following exposure to serum from depressed patients, where SSRI treatment leads to a return to baseline levels over time . Given that TGFβ is important for survival, homeostasis and barrier function of ECs, as well as angiogenesis, it is interesting that these drugs can elicit a time and dose‐dependent effect .…”
Section: Discussionmentioning
confidence: 97%
“…As previously mentioned, SSRIs have been shown to influence cell‐level phenotype, having been shown to modulate CAM expression mediated by a pro‐inflammatory response and in depressed patients . Given that CAMs are intercellular molecules, secretions of these proteins into solution indicates delocalization of the CAMs from cell–cell junctions to the surrounding solution, and thus damage to cell–cell junctions . A study by Lopez‐Vilchez et al showed that, over time, SSRIs reduced both cell surface ICAM expression and soluble VCAM expression in depressed patients back toward a healthy control, where both of these markers were significantly elevated over the healthy control with no treatment .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations